2021
DOI: 10.3389/fpubh.2021.612538
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Falls with Instability: An Analysis of Perceptions and Expectations toward the Use of Fall Detection Devices Among Older Adults in Malaysia

Abstract: Background: Falls are a significant incident among older adults affecting one in every three individuals aged 65 and over. Fall risk increases with age and other factors, namely instability. Recent studies on the use of fall detection devices in the Malaysian community are scarce, despite the necessity to use them. Therefore, this study aimed to investigate the association between the prevalence of falls with instability. This study also presents a survey that explores older adults' perceptions and expectation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…In view of the survey analysis, where respondents reported high prevalence of falls and balance instability, it is relevant to proceed with the proposed design process in regards to improve fall detection devices for older adults (Abdul Rahman et al, 2021). Also, majority of the respondents were interested to use such devices.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In view of the survey analysis, where respondents reported high prevalence of falls and balance instability, it is relevant to proceed with the proposed design process in regards to improve fall detection devices for older adults (Abdul Rahman et al, 2021). Also, majority of the respondents were interested to use such devices.…”
Section: Discussionmentioning
confidence: 99%
“…Referring to the study in Abdul Rahman et al (2021), the structure of study sample, sampling technique and the results of the survey were discussed. The study was done as the first part in the phases of the design process as illustrated in Figure 1.…”
Section: Questionnairementioning
confidence: 99%
See 2 more Smart Citations
“…The previous findings confirmed that lower limb strength and gait patterns differed between subjects with and without falls risk ( 12 , 13 ). Another former study provided insight into the association between balance function and falls risk, concluding that there was an increasing trend across age group in terms of the prevalence of falls and perceived instability among older adults ( X 2 = 20.145 and P -value < 0.001) ( 14 ). In conclusion, both fatigue and lower limb function can affect falls risk, while fatigue can predict lower limb function.…”
Section: Introductionmentioning
confidence: 99%